1992
DOI: 10.1093/oxfordjournals.eurheartj.a060311
|View full text |Cite
|
Sign up to set email alerts
|

Arterial elastic properties in man: a comparison of echo-Doppler indices of aortic stiffness

Abstract: Non-invasive assessment of mechanical properties of the aorta may prove useful in the early detection of atheroma. We have evaluated several of the available echocardiographic indices using ability to detect age-related changes in putatively disease-free vessels as a measure of sensitivity to changes in aortic mechanical properties. Suprasternal imaging was used in 49 healthy non-smoking volunteers to measure minimum and maximum aortic arch diameters. Maximal flow velocities, with corresponding acceleration ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
9

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 0 publications
3
96
0
9
Order By: Relevance
“…19 However, some studies have suggested that increase in large artery stiffness follows a nonlinear quadratic evolution, with more pronounced increase after the age of 55 years. 15,20,21 This result corroborates the well-known epidemiological observation of an increasing prevalence of systolic hypertension, the main clinical manifestation of large artery stiffness, after the age of 55 years. 7 The effect of gender is also controversial: some studies have shown a stronger increase of arterial stiffness in the elderly women, [22][23][24] whereas other studies suggest that the evolution of PWV was similar in the two genders.…”
Section: Introductionsupporting
confidence: 88%
“…19 However, some studies have suggested that increase in large artery stiffness follows a nonlinear quadratic evolution, with more pronounced increase after the age of 55 years. 15,20,21 This result corroborates the well-known epidemiological observation of an increasing prevalence of systolic hypertension, the main clinical manifestation of large artery stiffness, after the age of 55 years. 7 The effect of gender is also controversial: some studies have shown a stronger increase of arterial stiffness in the elderly women, [22][23][24] whereas other studies suggest that the evolution of PWV was similar in the two genders.…”
Section: Introductionsupporting
confidence: 88%
“…Some earlier studies showed that the pulse wave velocity through the descending aorta was higher in men than in women, 25 -26 suggesting stiffer aortas in men, but other reports have not found sex differences in either the pulse wave velocity 8 -9 -27 or the indexes of aortic stiffness based on direct imaging of aortic pulsations. 6 - 28 In our study, the aortic elastic modulus was independent of sex, and there also were no sex interactions, indicating that the regressions given in Tables 3 and 4 were not statistically significantly different between men and women.…”
Section: Potential Predictors Of Aortic Elastic Modulussupporting
confidence: 44%
“…Previous studies have shown a decrease in arterial compliance with advancing age, [5][6][7][8] in atherosclerosis and coronary heart disease, 5,10 -12 and in hypertension [13][14][15] and an increase in endurance-trained athletes. 6,16 -18 The difference observed between the 2 groups cannot be explained by the presence of any of these factors, because age, lipid profiles, resting mean arterial pressures, and aerobic fitness (quantified by VO 2 max) were comparable in the 2 groups.…”
Section: Discussionmentioning
confidence: 91%
“…Arterial compliance decreases with increasing age, [5][6][7][8] in atherosclerosis and coronary artery disease, 5,9 -12 and in hypertensive individuals. [13][14][15] Aerobic exercise has welldocumented efficacy for cardiovascular risk reduction, and it appears that at least part of its benefit derives from modification of arterial properties.…”
mentioning
confidence: 99%